Tantangan Pendidikan Multikultural di Indonesia di Zaman Serba Digital - Salsabila, Sonia Sinta; Rohmadani, Adinda Icha; Mahmudah, Safira Rona; Fauziyah, Nureza; Sholihatien, Rofa Afifah Noor (ANWARUL, 2022)
The purpose of writing this article is to identify the new challenges of multicultural education in the digital era, especially in Indonesia itself which is a country that has abundant diversity such as islands, languages, ethnicities, cultures and religions. Thus, this makes the rapid development of technology in this day and age. This of course can affect all existing aspects including the existing educational conditions, especially in multicultural education. The research method used in this research is to use a library research approach, namely collecting data collected from various documents such as academic journals, books, scientific works and others. From the results of research in a literature study, it can be shown that in the current digital era, multicultural education has a fairly serious impact where the rapid development of science and technology can trigger various conflicts and other problems if there is no awareness and high sensitivity to tolerate each other. each other.